Membrane-Assisted Cell Retention for Intensified Continuous Bioethanol Production - Tri Partono Adhi; Handika Prasetya Dwiyasni; Mirani Susiloputri; Reynard Reynard; Khoiruddin Khoiruddin; I Gede Wenten (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Continuous ethanol fermentation can achieve higher volumetric productivity than batch operation, but its performance is often limited by yeast washout, incomplete glucose conversion, and reduced fermentative activity under high-substrate and ethanol-stress conditions. This study evaluated an ultrafiltration membrane bioreactor for continuous ethanol fermentation using cell retention and controlled aeration. Glucose fermentation by Saccharomyces cerevisiae was evaluated in batch mode, conventional continuous anaerobic operation, anaerobic membrane bioreactor operation at dilution rates of 0.05 and 0.10 h⁻¹, and aerobic membrane bioreactor operation at 0.10 h⁻¹ with aeration rates of 0.08–0.30 vvm. Batch fermentation provided a reference for interpreting the continuous experiments: aerobic operation increased the final ethanol concentration from 65.7 to 89.5 g.L⁻¹ and the apparent maximum ethanol formation rate from 1.17 to 2.60 g.L⁻¹.h⁻¹, based on modified Gompertz fitting. In continuous operation, membrane-assisted cell retention reduced washout and increased biomass retention, glucose conversion, ethanol concentration, and volumetric productivity. At the same dilution rate of 0.10 h⁻¹, the anaerobic membrane bioreactor increased ethanol concentration from 2.8 ± 0.8 g.L⁻¹ to 43.4 ± 2.1 g.L⁻¹ and productivity from 0.3 ± 0.1 g.L⁻¹ h⁻¹ to 4.3 ± 0.2 g.L⁻¹.h⁻¹ relative to the non-membrane reactor. Lower dilution rate favored ethanol accumulation, whereas higher dilution rate favored volumetric productivity. Controlled aeration further enhanced productivity, reaching 5 g.L⁻¹.h⁻¹ at 0.08 vvm, but excessive aeration increased biomass accumulation while reducing ethanol yield and selectivity. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).